2020
DOI: 10.1007/s11910-020-01045-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunction in the Early Stages of Multiple Sclerosis—How Much and How Important?

Abstract: Purpose of Review Multiple sclerosis (MS) is a demyelinating disease of the central nervous system that mainly affects young adults and that is one of the leading causes of disability in this age group, with cognitive impairment occurring early in the course of the disease. This article summarizes the current knowledge about cognitive dysfunction in the early phase of MS, including biomarkers, MRI correlates, and its value as a prognostic marker. Recent Findings New sets of neuropsychological tests have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 84 publications
0
38
0
Order By: Relevance
“…The most frequently observed cognitive problems include deficits in information processing speed, episodic memory, complex attention, and executive function (8,10,11). The severity of cognitive impairment varies considerably among individuals and can be observed even in the early stages of the disease (12,13). Brain imaging studies have demonstrated that cognitive impairment in MS is related to the loss of brain volume or brain atrophy, which is an important sign of neurodegeneration (8,10).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently observed cognitive problems include deficits in information processing speed, episodic memory, complex attention, and executive function (8,10,11). The severity of cognitive impairment varies considerably among individuals and can be observed even in the early stages of the disease (12,13). Brain imaging studies have demonstrated that cognitive impairment in MS is related to the loss of brain volume or brain atrophy, which is an important sign of neurodegeneration (8,10).…”
Section: Introductionmentioning
confidence: 99%
“…CI might help in identifying patients at higher risk of disease progression in the long term [5,6], an aspect of paramount importance from a clinical perspective [7]. Crucially, the detection of initial CI in pwMS might be difficult, especially by using only paper-and-pencil tests [7,8]. It has been reported that Brain Sci.…”
Section: Introductionmentioning
confidence: 99%
“…CI has been reported in all stages and subtypes of MS and has been found to exert negative effects on employment, activities of daily living, and quality of life [ 3 , 4 ]. CI might help in identifying patients at higher risk of disease progression in the long term [ 5 , 6 ], an aspect of paramount importance from a clinical perspective [ 7 ]. Crucially, the detection of initial CI in pwMS might be difficult, especially by using only paper-and-pencil tests [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside typical measures of physical disability, additional tools assessing e.g. cognitive functions have been implemented in order to better describe the activity of MS (Oset et al, 2020).…”
Section: Introductionmentioning
confidence: 99%